2016
DOI: 10.1136/thoraxjnl-2016-209504
|View full text |Cite
|
Sign up to set email alerts
|

Chronotherapy for hypertension in obstructive sleep apnoea (CHOSA): a randomised, double-blind, placebo-controlled crossover trial

Abstract: ACTRN12611000216910, Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…In contrast to the above studies, a RCT in patients with moderate to severe OSA and HTN showed that an ACEI taken at night did not further reduce nocturnal SBP compared with morning dosing (−6.9 mmHg, −8.0 mmHg, respectively); regardless of the addition of CPAP, which similarly lowered sleep SBP both with morning and evening dosing (142). Morning compared to evening administration of the ACEI was also superior at reducing daytime SBP.…”
Section: Resultsmentioning
confidence: 90%
“…In contrast to the above studies, a RCT in patients with moderate to severe OSA and HTN showed that an ACEI taken at night did not further reduce nocturnal SBP compared with morning dosing (−6.9 mmHg, −8.0 mmHg, respectively); regardless of the addition of CPAP, which similarly lowered sleep SBP both with morning and evening dosing (142). Morning compared to evening administration of the ACEI was also superior at reducing daytime SBP.…”
Section: Resultsmentioning
confidence: 90%
“…In the MAPEC study, chronotherapy improved nocturnal blood pressure and led to a 17% reduction in cardiovascular risk for each 5 mm Hg reduction in systolic blood pressure during sleep (p<0.001) in patients with essential hypertension 15. The negative findings by Serinel et al 12 demonstrate that such results cannot be extrapolated to the OSA population. While CPAP is the gold standard treatment for OSA, it is not necessarily effective in reducing blood pressure, particularly if adherence to treatment is low.…”
mentioning
confidence: 96%
“…The study presented in this issue of Thorax by Serinel et al 12 attempted to address one piece of the puzzle regarding a better strategy for managing OSA-related hypertension. Using a well-established cross-over randomised controlled trial design, the authors explored whether chronotherapy would be of particular benefit in hypertensive patients with OSA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the intervention, according to the MAPEC authors, appears to be particularly appropriate in diabetics, 6 those with chronic kidney disease (CKD), 7 those with nocturnal hypertension, but not those with obstructive sleep apnoea (OSA). 8 There is clearly scope to repeat a trial similar to MAPEC in a UK general practice population. These trials also raise questions about the use and funding of 24-hour ambulatory BP monitoring not just for diagnosis, but also for monitoring.…”
Section: What Is the Evidence?mentioning
confidence: 99%